Identificação de áreas potenciais à mariscultura em Paraty/RJ com uso de um sistema de informações geográficas (SIG) - Lima, Cristiano Figueiredo (2008)
Considering the scenario of over-exploration and degradation of the coastal resources in several parts of the word, the mariculture activity has played an important role as an alternative solution for the sustainable development of coastal communities. Paraty, located in the Bay of Ilha Grande, at the Fluminense Southern Cost, has singular environmental characteristics, both social and physical, from the point of view of preservation, besides the potential for the development of this activity. This study, of interdisciplinary character, has been divided into three steps: characterization of mariculture in global, regional and local levels; survey methodologies for the demarcation of potential areas for mariculture; and the delimitation of these areas for the development of the three species most cultivated in Rio de Janeiro: Vieira or Coquille Saint Jacques or Nodipecten nodosus (Linnaeus), Perna perna mussels and Crassostrea rhizophorae oyster or swamp´s oyster. The study was based on secondary data, although some relevant data has been collected in field, through the methodology of participatory mapping. The use of the Geographic Information System (GIS) for the evaluation and representation of data, allowed the spatialization and the representation of these data in maps. Therefore, this work aims to contribute to the development of mariculture in Paraty, serving as a tool for managers, fishermens and others interested in this activity, as well as for the characterization of the environment in the council. The result show both production and restrictive indicators, that most influence the cultivation of the organisms cited in Paraty. Among production indicators we find: depth, temperature, oceanographic indicators (ocean streams and waves) and the cultivation access to villages and communities of caiçaras. Among restrictive indicators we find: the Units of Conservation of Integral Protection located in the marine environment, the pollution of water resourcers and activities with potential conflicts.